GAMBARAN CONTINUITY OF CARE DALAM PELAYANAN KEBIDANAN PADA KEHAMILAN FISIOLOGIS DI PUSKESMAS SELOPAMPANG KABUPATEN TEMANGGUNG - Inayah, Inayah (Universitas Muhammadiyah Surabaya, 2023)
Objective: Â Continuity of Care care is continuous care from pregnancy to Family Planning as an effort to reduce MMR & IMR. The effort to implement Continuity Of Care in Indonesia is done by providing comprehensive and quality health services to mothers and babies within the scope of midwifery, namely conducting midwifery care on an ongoing basis (continuity of care). This is the strategic plan of the minister of health from one of the health development priorities. This study aims to determine COC services in midwifery services in physiological pregnancy at Selopampang Primary Health Center, Temanggung Regency. Methods: Â This research employed a qualitative research. The data were collected through interviews with informants. The informants in this study included 5 midwives and 4 pregnant women as respondents. Results: Â The results of the study found that services were in accordance with COC and in accordance with government policies but there were obstacles in service, namely the lack of midwives.Conclusion: Midwives should maintain and improve the quality of services for pregnant women by taking into account SOP and government policies and the need for additional midwives to help improve the performance of health workers at primary health centers